Polyamine-based analogues as biochemical probes and potential therapeutics. (20th March 2007) - Boncher, T.; Bi, X.; Varghese, S.; Casero, R.A.; Woster, P.M.
Abstract : The polyamines putrescine, spermidine and spermine are ubiquitous polycationic compounds that are found in nearly every cell type, and are required to support a wide variety of cellular functions. The existence of multiple cellular effector sites for naturally occurring polyamines implies that there are numerous targets for polyamine-based therapeutic agents. Through a programme aimed at the synthesis and evaluation of biologically active polyamine analogues, our laboratory has identified three distinct structural classes of polyamine derivatives that exhibit promising biological activity in vitro . We have synthesized more than 200 symmetrically and unsymmetrically substituted alkylpolyamines that possess potent antitumour or antiparasitic activity, depending on their backbone architecture and terminal alkyl substituents. Along similar lines, we have developed novel polyamino(bis)guanidines and polyaminobiguanides that are promising antitrypanosomal agents and that interfere with biofilm formation in the pathogenic bacterium Yersinia pestis . Finally, we recently reported a series of PAHAs (polyaminohydroxamic acids) and PABAs (polyaminobenzamides) that inhibit HDACs (histone deacetylases), and in some cases are selective for individual HDAC isoforms. These studies support the hypothesis that polyamine-based small molecules can be developed for use as biochemical probes and as potential therapies for multiple diseases.